The Role of Rolling Door Patrols in Reducing the Risk of Theft with Weighting in Tuban Police Area - Samosir, Muhammad Rido Pratama; Althaf, Kevin Icasia; Farid, Muhammad Imam (Akademi Kepolisian Republik Indonesia, 2024)
Aggravated theft poses a serious threat to public safety and social stability in urban areas. The Tuban District Police, as the law enforcement agency in the region, continuously strives to enhance security and reduce the risk of aggravated theft. One of the implemented strategies is the Rolling Door patrol, an innovative surveillance method aimed at reducing the vulnerability of shops and small businesses to such criminal activities.This study aims to analyze the role of Rolling Door patrols in reducing the risk of aggravated theft in the Tuban District Police area. The research method employed is descriptive analysis, collecting data on aggravated theft incidents before and after the implementation of Rolling Door patrols. The gathered data includes the number of incidents, locations, times, and the modus operandi used by perpetrators.The results indicate that the implementation of Rolling Door patrols effectively reduces the risk of aggravated theft in the Tuban District Police area. Before the patrols, there was a significant upward trend in aggravated theft incidents, whereas after their implementation, a notable decrease in incidents occurred. Data analysis reveals that locations previously targeted by aggravated thieves experienced a decrease in incidents following the regular implementation of Rolling Door patrols.